Testing a molecular protocol to monitor the presence of golden mussel larvae (Limnoperna fortunei) in plankton samples - Boeger, Walter A. (2007)
The golden mussel (Limnoperna fortunei, Mollusca: Mytilidae) is an emerging invasive species in freshwater environments in South America, causing extensive environmental and economic impacts. A molecular method to detect larvae of the golden mussel in plankton samples has been recently developed and holds promise for becoming an important way to monitor the expansion of golden mussel populations. In the present study, we conduct, for the first time, field tests of this method by comparing its performance with alternative sampling efforts (microscopy and manual search for adults). In addition, we test different modifications of the molecular method to deal with PCR inhibition in environmental samples. The results indicate that the molecular method is very efficient, being faster and more sensitive that microscopy methods. Therefore, the molecular method tested in the present study can represent an invaluable tool in large-scale monitoring efforts of the golden mussel throughout its introduced range.